PENGENDALIAN MANAJEMEN DALAM MENINGKATKAN KINERJA PADA USAHA MAKANAN RINGAN KERIPIK PISANG “DANGKRIK” DUSUN KULUBANYU, MOJOKERTO - Yosef Yovan Paskah Andika (Sekolah Tinggi Pariwisata Mataram, 2022)
The village is part of an area that has a low level of economic understanding. Therefore, populist-based economic movements are often applied to economic development in rural areas. Processing of produce, agriculture, estate, and livestock into finished goods with a higher selling value will greatly help the village community improve its economic level. The development of the village, economy is not easy to do, because the products produced still have to compete again with other manufacturers and other similar products. This is what encourages efforts to conduct research and assistance to the people of Kulubanyu Hamlet to develop processed products, sell and compete in the market, and manage and enlarge their business units. It is necessary to encourage this to be carried out in village building activities held for approximately 6 months by involving the people of Kulubanyu Hamlet, especially housewives. It is hoped that the writing of this article can improve the control of the banana chip snack business business